Hyaluronic acid three‐dimensional scaffold for surgical revision of retracting scars: a human experimental study. Issue 3 (28th May 2012) - Faga, Angela; Nicoletti, Giovanni; Brenta, Federica; Scevola, Silvia; Abatangelo, Giovanni; Brun, Paola
<x xml:space="preserve">Abstract</x> An observational study was carried out at the Plastic and Reconstructive Surgery Unit of the University of Pavia – Salvatore Maugeri Research and Care Institute, Pavia, Italy, to assess the clinical and histological long‐term outcomes of autologous skin grafting of fresh surgical wounds following previous repair with a hyaluronic acid three‐dimensional scaffold (Hyalomatrix®). Eleven fresh wounds from surgical release of retracted scars were enrolled in this study. A stable skin‐like tissue cover was observed in all of the treated wounds in an average 1 month's time; at the end of this study, after an average of 12 months' time, all of the reconstructed areas were pliable and stable, although an average retraction rate of 51·62% was showed. Histological observation and immunohistochemical analysis displayed integration of the graft within the surrounding tissues. A regenerated dermis with an extracellular matrix rich in type I collagen and elastic fibres and with reduced type III collagen rate was observed. The epidermis and dermoepidermal junction featured a normal appearance with well‐structured dermal papillae, too. Although the histological features would suggest regeneration of a skin‐like tissue, with a good dermis and no signs of scarring, the clinical problem of secondary contracture is still unsolved.